Ghost-spider. Broken chords : a Spider-Verse graphic novel - Brown, Roseanne A. (Graphix, an imprint of Scholastic, 2026)
"Gwen Stacy does her best to balance being a student, playing in her punk band, and fighting crime as the super hero Ghost-Spider. But when Arachnid, a super villain from a different dimension with similar spider powers, attacks her world, Ghost-Spider will have to team up with a new ally-Spider-Punk! Can these two get to the truth behind Arachnid's attacks? And just how did Gwen's family history get webbed into this?"--